2014
DOI: 10.1111/ejn.12720
|View full text |Cite
|
Sign up to set email alerts
|

Excessive disgust caused by brain lesions or temporary inactivations: mapping hotspots of the nucleus accumbens and ventral pallidum

Abstract: Disgust is a prototypical type of negative affect. In animal models of excessive disgust, only a few brain sites are known in which localized dysfunction (lesions or neural inactivations) can induce intense ‘disgust reactions’ (e.g., gapes) to a normally pleasant sensation such as sweetness. Here we aimed to map forebrain candidates more precisely to identify where either local neuronal damage (excitotoxin lesions) or local pharmacological inactivation (muscimol-baclofen microinjections) caused rats to emit ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 133 publications
(214 reference statements)
5
65
0
Order By: Relevance
“…Amygdala enhanced connection with the olfactory (pyriform) cortex is clearly coherent with the ancestral origin of disgust that is anchored on chemical senses, and fits well with behavioural evidence that recognition of disgusted faces is improved by the presentation of an olfactory stimulus irrespective of its emotional valence90. Amygdala integration with the NAc and ventral pallidum (VP) finds direct support in rodent studies on disgust, showing that lesions and temporary inactivation of either structures generate intense sensory disgust91. The thalamus has been found to respond selectively to disgust in meta-analyses310 or to images of rotten food and mutilation92, whereas MVPA found that voxels within the thalamus, especially the ventral anterior nuclei, are particularly accurate in classifying disgust movies clips6.…”
Section: Discussionsupporting
confidence: 74%
“…Amygdala enhanced connection with the olfactory (pyriform) cortex is clearly coherent with the ancestral origin of disgust that is anchored on chemical senses, and fits well with behavioural evidence that recognition of disgusted faces is improved by the presentation of an olfactory stimulus irrespective of its emotional valence90. Amygdala integration with the NAc and ventral pallidum (VP) finds direct support in rodent studies on disgust, showing that lesions and temporary inactivation of either structures generate intense sensory disgust91. The thalamus has been found to respond selectively to disgust in meta-analyses310 or to images of rotten food and mutilation92, whereas MVPA found that voxels within the thalamus, especially the ventral anterior nuclei, are particularly accurate in classifying disgust movies clips6.…”
Section: Discussionsupporting
confidence: 74%
“…Scopolamine microinjections throughout nearly the entire NAc medial shell also doubled the number of 'disgust' reactions elicited by bitter quinine. However, scopolamine's induction of negative affect was never strong enough to actually create 'disgust' reactions to the sweet taste of sucrose (unlike GABA stimulations in caudal shell, which can reverse sucrose reactions from 'liking' to 'disgust' (Faure et al, 2010;Ho and Berridge, 2014;Reynolds and Berridge, 2002)). Finally, ACh blockade by scopolamine specifically in the caudal half of medial shell additionally elicited fear-related defensive treading behavior, which was directed toward locations in the chamber that may have been perceived as more threatening than others (eg, light-reflecting corners).…”
Section: Discussion Overviewmentioning
confidence: 97%
“…S. Smith & Berridge, 2007). In addition to enhancing ‘liking’ for intense pleasure, this ventral pallidal hotspot is the only known site in the brain where a small lesion conversely also eliminates normal pleasure, and reverses the hedonic impact of sweet sensation from ‘liked’ to instead ‘disgusting’ (so that afterwards sucrose elicits bitterness-typical gapes and related negative expressions) (Berridge & Kringelbach, 2015; Ho & Berridge, 2014). …”
Section: So Where Does ‘Liking’ Come From In the Brain?mentioning
confidence: 99%